Improving phosphorus use efficiency in groundnut with microbial cultures: Improving phosphorus use efficiency in groundnut with microbial cultures - S THIRUVARASSAN (Journal of Oilseeds Research, 2023)
Field experiments were carried out during 2018 to 2021 at Oilseeds Research Station, Tindivanam, to study the improved phosphorus use efficiency in groundnut with microbial culture. The results revealed that higher mean pod yield (2581 kg/ha) was recorded in the treatment that involved application of 40 kg/ha of P + DGRC culture which was on par with the treatment T4, that involved application of 60 kg/ha of Phosphorus. Control recorded the lowest yield.